Memories of post-imperial nations: silences and concerns - Rothermund, Dietmar (India quarterly, 2014)
Seven nations lost their colonial empires after the World War II. Italy and Japan had to relinquish their colonies immediately after the war. Great Britain granted independence to India in 1947 and released most of its African colonies in 1960. France and the Netherlands reclaimed their colonies after recovering their sovereignty after the war, but they had to abandon them nevertheless after intense struggles. Belgium shared the same fate. Only Portugal clung to its 'overseas provinces' until 1974 when democratisation and decolonisation coincided. Scholars representing these seven nations met at Heidelberg University in May 2013 to compare notes concerning the post-imperial memories of their nations. The conference was supported by the Robert Bosch Foundation, Stuttgart. The period after decolonisation was characterised by long silences in the post-imperial nations. It is only in recent times that intensive debates of the imperial past and its conflicting memories have been conjured up.